THE EFFECTS OF GRAMMAR MASTERY AND READING INTEREST TOWARDS WRITING DESCRIPTIVE TEXT ABILITY - Neneng Misliyah (Universitas Indraprasta PGRI, 2019)
The purpose of this research is to find out and analyze the effects of grammar mastery and reading interest towards writing desctiptive text ability. The population that is observed in this research is students of class VIII (Eight) SMP Negeri East Jakarta. The sample is 72 respondents from 3 schools. The sample is obtained through a simple random sample, that is the researcher combined respondents in the population so that they would be measured in the same amount. This study has 3 variables which are divided into 2 independent variables (variable grammar mastery and reading interest variable) and 1 dependent variable (descriptive writing ability variable). Data collection is done through multiple choice tests, questionnaires and written tests for all variables. Data acquisition is then analyzed using multiple correlation and regression techniques. Before performing a regression test, the test of analysis requirements must be achieved first, such as normality test and linearity test. The results of this study are 1) There is a significant effect of gramma mastery and reading interest together toward writing desctiptive text ability of SMP Negeri students East Jakata.. This is evidenced by the sig score. 0.003 <0.05 and F_ count = 6.416; 2) There is an insignificant effect of grammar mastery towards writing desctiptive text ability of SMP Negeri students East Jakarta.. This is evidenced by the sig score. 0.729> 0.05 and tcount = -.347 .; 3) There is a significant effect of reading interest towards writing desctiptive text ability of SMP Negeri students East Jakarta.. This is evidenced by sig score 0.001 <0.05 and tcount = 3,578. This shows that writing desctiptive text ability is highly mastered or effected by the mastery of grammar and reading interest what they have.Keywords: Grammar Mastery, Reading Interest, writing desctiptive text ability